6 Axiomatic Derivations

We now present an axiom system for propositional logic, which will consist of an infinite set of axioms and a single rule of inference. A derivation of a well-formed formula from a set of formulas will consist of a finite sequence of formulas each of whose members will either be an axiom or a premise or the output of an application of the rule of inference to prior members of the sequence.

There is one ingredient we will use for the specification of the infinite set of axioms. If φ is a propositional formula whose propositional variables are p1,...,pn and ψ1, …, ψn are propositional formulas, we write φ[ψ1/p1,...,ψn/pn] for the well-formed formula that results from φ when each propositional variable pi is substituted for the well-formed formula ψi. We will call φ[ψ1/p1,...,ψn/pn] a substitution instance of φ.

Definition 6.1 (Uniform Substitution) Given a well-formed formula φ whose propositional variables are among p1,,pn and well-formed formulas ψ1,,ψn, define φ[ψ1/p1,...,ψn/pn] inductively:

  • If φ is pi, φ[ψ1/p1,...,ψn/pn] is ψi.

  • If φ is ¬χ, φ[ψ1/p1,...,ψn/pm] is ¬χ[ψ1/p1,...,ψn/pm].

  • If φ is (χρ), then φ[ψ1/p1,...,ψn/pn] is (χ[ψ1/p1,...,ψn/pn]ρ[ψ1/p1,...,ψn/pn]).

We are now in a position to define the set of axioms of the system:

Definition 6.2 (Axiom) A well-formed formula φ is an axiom if, and only if, it is a substitution instance of one of the well-formed formulas below: A1p(qp)A2(p(qr))((pq)(pr))A3(¬p¬q)((¬pq)p)

We will use a single rule of inference, which we call Modus Ponens (MP). The rule in question will enable us to move from two formulas of the form φ and (φψ) to the formula ψ.

(MP)φ, (φψ)/ψ

Definition 6.3 (Derivability) A well-formed formula φ is derivable from a set of well-formed formulas Γ, written Γφ, if, and only if, there is a finite sequence of well-formed formulas (χ1,,χn) such that

  • χn=φ

  • for each mn, either

    • χm is an axiom, or
    • χmΓ, or
    • χk=(χlχm), for some k,l<m.

Such a finite sequence (χ1,...,χn) is called a derivation (or a proof) of φ from Γ.

So, a formula appears in a derivation if, and only if, it is either an axiom or a premise or the output of an application of modus ponens to two earlier members of the sequence.

Definition 6.4 (Theorem) A well-formed formula φ is a theorem, written φ, if, and only if, φ.

We will write φ to indicate that φ is not a theorem.

Here is a simple example of a derivation:

Example 6.1 pp 1p((pp)p)A1[p/p,(pp)/q]2(p((pp)p))((p(pp))(pp))A2[p/p,(pp)/q,p/r]3(p(pp))(pp)MP 1,24p(pp)A1[p/p,p/q]5ppMP 3,4

It is not difficult to generalize this argument into a schematic derivation of φφ from no premises: φφ We will soon develop a library of subroutines, which will facilitate the discussion of the question of whether a given formula is derivable from a set of formulas.

The Deduction Theorem

We will rely on a very general result. First, some notational conventions. We write Γ,φ to abbreviate: Γ{φ}. And we will similarly write φψ to abbreviate: {φ}ψ.

Theorem 6.1 Given a set of well-formed formulas Γ and two well-formed formulas φ and ψ, Γ,φψ if, and only if, Γφψ.

One direction is simple:

Theorem 6.2 Given a set of well-formed formulas Γ and two well-formed formulas φ and ψ, if Γφψ, then Γ,φψ.

Proof. To obtain a derivation of ψ from Γ,φ, we may extend a derivation of φψ from Γ with two additional steps: φ, which being a member of Γ,φ, is available as a premise, and ψ which is the output of Modus Ponens when applied to φψ and φ.

The other direction is the deduction theorem, which requires a more involved justification:

Theorem 6.3 (The Deduction Theorem) Given a set of well-formed formulas Γ and two well-formed formulas φ and ψ, if Γ,φψ, then Γφψ.

Proof. Choose a set of formulas Γ and a formula φ. We will use a complete induction on n to prove that for every non-zero n:

  • if (χ1,...,χn) is a derivation of ψ from Γ,φ, then Γφψ.

That is, we argue that

  • if that is true for every m<n, then it is true for n as well,

So, we begin with the assumption:

  • for every m<n, if (χ1,...,χm) is a derivation of a formula ψ from Γ,φ, then Γφψ

We want to prove that

  • if (χ1,...,χn) is a derivation of a formula ψ from Γ,φ, then Γφψ.

Consider a derivation of ψ from Γ,φ of the form: (χ1,...,χn) That means that χn=ψ.

There are four cases to consider:

Case 1. ψ is a logical axiom.

Here is a derivation of φψ from Γ: 1ψ(φψ)A1[ψ/p,φ/q]2ψ3φψMP 1,2

Case 2. ψΓ

Here is a similar derivation of φψ from Γ: 1ψ(φψ)A1[ψ/p,φ/q]2ψ3φψMP 1,2 Case 3. ψ=φ

Since φφ, a derivation of φφ is a derivation of φψ from Γ. Therefore Γφψ.

Case 4. χk=(χlψ) for some k,l<n

That means that (χlψ) and χl are each in the sequence, which means that there are derivations (χ1,χlψ) and (χ1,,χl) of each formula χlψ and χl from Γ,φ of length <n.

Since both derivations have length strictly less than n, by inductive hypothesis, Γφ(χlψ) and Γφχl.

To build a derivation of φψ from Γ, we may concatenate derivations of φ(χ1ψ) and φχl, respectively, from Γ: ...kφ(χlψ)Γφ(χlψ)mφχlΓφχln((φ(χ1ψ))((φχl)(φψ))A2[φ/p,χl/q,ψ/r]n+1(φχl)(φψ)MP k,nn+2φψMP m,n+1 We conclude that given Γ and φ, if (χ1,...,χn) is a derivation of a formula ψ from Γ,φ, then Γφψ.

The deduction theorem encodes a common method of proof in mathematics. When you want to establish a conditional φψ in a mathematical context, you may adjoin φ to the body of mathematical assumptions in place Γ and once ψ is justified on that basis, you may conclude that φψ is a deductive consequence of the original assumptions.

We will now make use of the Deduction Theorem in order to prove a variety of helpful facts, which will facilitate the use of the axiom system.

Lemma 6.1 (φψ)((ψχ)(φχ))

Proof. Given the Deduction Theorem, it suffices to note: {φψ}(ψχ)(φχ). But given the Deduction Theorem, this reduces to: {φψ,ψχ}φχ, and {φψ,ψχ,φ}χ. But it is simple to provide a derivation of χ from {φψ,ψχ,φ}: 1φψPremise2φPremise3ψMP 1,24ψχPremise5χMP 3,4

Lemma 6.2 (¬ψ¬φ)(φψ)

Proof. Given the Deduction Theorem, it suffices to note: {¬ψ¬φ}φψ, which would in turn follow from the observation: {¬ψ¬φ,φ}ψ. We provide a derivation of ψ from {¬ψ¬φ,φ}: 1¬ψ¬φPremise2φ(¬ψφ)A1[φ/p,¬ψ/q]3φPremise4¬ψφMP 2,35(¬ψ¬φ)((¬ψφ)ψ)A3[ψ/p,φ/q]6(¬ψφ)ψMP 1,57ψMP 4,6

Lemma 6.3 ¬¬φφ

Proof. Given the Deduction Theorem, it suffices to note: ¬¬φφ Here is a derivation of φ from ¬¬φ: 1¬¬φ(¬φ¬¬φ)A1[¬¬φ/p,¬φ/q]2¬¬φPremise3¬φ¬¬φMP 1,24(¬φ¬¬φ)((¬φ¬φ)φ)A3[φ/p,¬φ/q]5(¬φ¬φ)φMP 3,46¬φ¬φ¬φ¬φ7φMP 5,6

Lemma 6.4 φ¬¬φ

Proof. We exploit the last two observations to produce a simple derivation of φ¬¬φ: 1¬¬¬φ¬φLemma 3.32(¬¬¬φ¬φ)(φ¬¬φ)Lemma 3.23φ¬¬φMP 1,2

Lemma 6.5 (φψ)(¬ψ¬φ)

Proof. Given the Deduction Theorem, it suffices to establish: {φψ}¬ψ¬φ, and {φψ,¬ψ}¬φ. Here is a derivation of ¬φ from {φψ,¬ψ}: 1φψ2ψ¬¬ψLemma 3.43¬¬φφLemma 3.34(¬¬φφ)((φψ)(¬¬φψ))Lemma 15(φψ)(¬¬φψ)MP 3,46¬¬φψMP 1,47(¬¬φψ)((ψ¬¬ψ)(¬¬φ¬¬ψ))Lemma 4.18(ψ¬¬ψ)(¬¬φ¬¬ψ)MP 6,79¬¬φ¬¬ψMP 2,810(¬¬φ¬¬ψ)(¬ψ¬φ)Lemma 3.211¬ψ¬φMP 9,10

Exercise 6.1 Use these lemmas in order to justify: (φ¬φ)¬φ

Lemma 6.6 ¬φ(φψ)

Proof. Given the Deduction Theorem, it suffices to show: {¬φ,φ}ψ Here is an outline of a derivation of ψ from {¬φ,φ}: 1¬φ(¬ψ¬φ)A1[¬φ/p,¬ψ/q]2¬φPremise3(¬ψ¬φ)MP 1, 24φψ3, Lemma 3.25φPremise6ψMP 4, 5

Maximal Consistency

Definition 6.5 (Consistency) A set of formulas Γ is consistent if, and only if, is not derivable from Γ. That is, Γ is consistent if, and only if, Γ.

We write that a set Γ is inconsistent if, and only if, Γ is not consistent. That is, Γ is inconsistent if, and only if, Γ. Recall the definition of in terms of : :=¬. Since is an abbreviation for the formula pp, is an abbreviation for ¬(pp).

Proposition 6.1 Given a set of formulas Γ and a formula φ, ΓφiffΓ,¬φ  is inconsistent.

Proof. We discuss one direction at a time.

() We argue that if Γφ, then Γ,¬φ.

To that purpose we use the fact that a derivation of φ from Γ is automatically a derivation of φ from the larger set Γ,¬φ. We use this fact to produce a derivation of from Γ,¬φ. 1¬φ(¬¬φ)A1[¬φ/p,/q]2¬φPremise3¬¬φMP 1, 24φ3, Lemma 3.25φΓ,¬φφ6MP 4, 5

() We want to prove that if Γ,¬φ, then Γφ.

We use the Deduction Theorem to move from Γ,¬φ to Γ¬φ. Since Γ,¬φ, by lemma 3.4, Γ,¬φ¬¬, which means Γ,¬φ¬. So, by the Deduction Theorem, Γ¬φ¬.

We now outline a derivation of φ from Γ: 1¬φ¬Γ¬φ¬2(¬φ¬)((¬φ)φ)A3[φ/p,/q]3(¬φ)φMP 1, 24¬φΓ¬φ5φMP 3, 4

We now define what is for a set of formulas to be maximal consistent.

Definition 6.6 (Maximal Consistency) A set of formulas Γ is maximal consistent if, and only if,

  1. Γ is consistent, and

  2. for every φ, if Γ,φ is consistent, then φΓ.

Proposition 6.2 Given a maximal consistent set of formulas Γ and two formulas φ and ψ,

  1. Γφ if, and only if, φΓ.

  2. ¬φΓ if, and only if, φΓ.

  3. φψΓ if, and only if φΓ or ψΓ.

Proof. Given a maximal consistent set of formulas Γ and two formulas φ and ψ, consider each claim at a time.

  1. Γφ if, and only if, φΓ.

() We argue that if Γφ, then φΓ.

Suppose Γφ. We proceed by reductio. Suppose φΓ. By definition of maximal consistency, if Γ is maximal consistent and φΓ, then Γ,φ is inconsistent. But since Γφ, by proposition 3.6, Γ,¬φ is inconsistent as well. It follows that Γ is inconsistent, which contradicts its maximal consistency.4 This is problem 3 in assignment 2. We conclude that φΓ.

() We argue that if φΓ, then Γφ.

If φΓ, then there is a one-line derivation of φ from Γ.

  1. ¬φΓ if, and only if, φΓ.

() We argue that if ¬φΓ, then φΓ.

Suppose ¬φΓ. Then, by 1 above, Γ¬φ. Since Γ is consistent, Γφ, which, by 1 above, means φΓ.5 If Γφ and Γ¬φ, then Γ. This is because by lemma 3.6, Γ¬φ(φ).

() We show that if φΓ, then ¬φΓ.

Suppose φΓ. Since Γ is maximal consistent, Γ,φ is inconsistent. Given lemmas 3.3 and 3.4, Γ,φ is inconsistent if, and only if, Γ,¬¬φ is inconsistent. So, since Γ,¬¬φ is inconsistent, we conclude, by proposition 3.6, that Γ¬φ. So, by 1 above, ¬φΓ.

  1. φψΓ if, and only if φΓ or ψΓ.

() We argue that if φψΓ, then if φΓ, then ψΓ.

Suppose φψΓ. Then, given 1 above, Γφψ. Now: if φΓ, then Γφ and Γψ, whence ψΓ.

() We show that if φΓ or ψΓ, then φψΓ.

Suppose φΓ or ψΓ.

If φΓ, then given 2 above, ¬φΓ. Since lemma 3.6 gives us that ¬φ(φψ) and Γ¬φ, we infer Γφψ. So, given 1, φψΓ.

If ψΓ, then since ψ(φψ), Γφψ. So, given 1, φψΓ.